“On-oﬀ” switchable tool for food sample preparation: merging molecularly imprinting technology with stimuli-responsive blocks. Current status, challenges and highlighted applications - Garcia, Raquel (2017)
Sample preparation still remains a great challenge in the analytical workﬂow representing the most timeconsuming and laborious step in analytical procedures. Ideally, sample pre-treatment procedures must be more selective, cheap, quick and environmental friendly. Molecular imprinting technology is a powerful tool in the development of highly selective sample preparation methodologies enabling to preconcentrate the analytes from a complex food matrix. Actually, the design and development of molecularly imprinted polymers-based functional materials that merge an enhancement of selectivity with a controllable and switchable mode of action by means of speciﬁc stimulus constitutes a hot research topic in the ﬁeld of food analysis. Thus, combining the stimuli responsive mechanism and imprinting technology a new generation of materials are emerging. The application of these smart materials in sample preparation is in early stage of development, nevertheless new improvements will promote a new driven in the demanding ﬁeld of food sample preparation. The new trends in the advancement of food sample preparation using these smart materials will be presented in this review and highlighted the most relevant applications in this particular area of knowledge